Course Reform of Metal Cutting Machine Tool Design under the Background of Engineering Education Accreditation - Yang, Jianjun; Lan, Hongbo; Zhu, Xiaoyang (Advances in Social Sciences Research Journal, 2020)
The course of metal cutting machine tool design is a compulsory course in the manufacturing direction of mechanical specialty in our university. Under the background of engineering education accreditation, the course has been reformed. The new syllabus corresponding to the index points of graduation requirements was established, the teaching contents were integrated and optimized, project teaching method and diversified assessment method were designed, the evaluation method of course objectives achievement was constructed, the closed-loop course quality assurance system of Design-Implementation-Assessment-Evaluation-Improvement was formed. Students’ learning initiative and the learning effect are improved.